"A Good Deal of Intensity": On the Development of Degree and Quantity Modifier Good. (June 2021) - Ghesquière, Lobke
This paper explores how the originally descriptive adjective good (e.g., "a good man") developed degree modifier (e.g., "a good scolding") and quantity modifier (e.g., "a good many people") uses. The work is innovative in exploring the intensification potential of unbounded rather than bounded adjectives and in distinguishing between degree and quantity modification, the latter only recently gaining attention in the cognitive-functional literature. The developmental path of good will be linked to its construal in terms of scalarity, the process of subjectification, and the categorial shift from modification to submodification.